(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: To evaluate the results of treatment and care for patients with COPD exacerbations at the Department of Respiratory Internal Medicine - Saint Paul General Hospital. Methods: 121 subjects with COPD were monitored and assessed the nursing care process upon admission and discharge. Results: The proportion of patients ≥ 60 years old (85.8%); men 61.5%; COPD duration of 2 to 5 years 56.4%. The smoking rate was 70.5%, tobacco 47.4%, pipe tobacco 47.4%, and quit smoking accounted for 63.1%. Upon admission and discharge, patients with COPD receive adequate care regarding vital signs and health status, nutritional care and rehabilitation support, and health education. The rate of patients receiving good care at the time of admission was 87.4%; at the time of discharge was 91.6%. Conclusion: Patients with COPD receive adequate care regarding vital signs and health status, support nutritional care, and rehabilitation function during hospitalization and discharge. Most patients receive good nursing care.